La globalización del periodismo científico bajo patrones anglosajones: un estudio de caso en la periferia - Cortiñas Rovira, Sergi (Estudios sobre el Mensaje Periodístico, 2007)
Scientific journalism is a fundamental tool to guarantee freedom and democracy in a society based on knowledge like the one we live in nowadays. This paper tries to reason the causes and consequences of the phenomenon of the globalisation of scientific journalism in the world, which is every day more and more spread. From the Second World War the Anglo-Saxon model has been the dominant paradigm in the popularisation of sciences and the Anglo-Saxon strategies and methods have caught on all the continents. One of the best examples in continental Europe of this globalising tendency is the journalist of the main Spanish newspaper El País Javier Sampedro, whose work is strongly marked by Anglo-Saxon influences. This paper is based on the author’s PhD thesis.